1977
DOI: 10.1073/pnas.74.12.5569
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin stimulation of bovine adrenocortical cell growth.

Abstract: Factors controlling proliferation of adrenocortical cells have been studied in Although several purified polypeptides have been reported to stimulate the proliferation of animal cells-in culture, a high degree of cell specificity has not been observed. Fibroblast growth factor (FGF) is mitogenic for fibroblast, adrenocortical, myoblast, smooth muscle, chondrocyte, vascular endothelial, granulosa, and luteal cells, whereas epidermal growth factor (EGF) is mitogenic for fibroblast, corneal epithelial, certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…Accordingly, the mechanism of thyroxine-induced renal hypertrophy involves the activation of circulating or intrarenal RAS, which is mediated by the upregulation of renal expression of renin mRNA. It is well known that ANG II has potent cell proliferation effects in vitro (Gill et al 1977) and in vivo (Casellas et al 1997). Therefore, it is understandable that activation of RAS caused renal hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the mechanism of thyroxine-induced renal hypertrophy involves the activation of circulating or intrarenal RAS, which is mediated by the upregulation of renal expression of renin mRNA. It is well known that ANG II has potent cell proliferation effects in vitro (Gill et al 1977) and in vivo (Casellas et al 1997). Therefore, it is understandable that activation of RAS caused renal hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…As well, ANG II plays a prime role in the regulation of blood pressure because of its potent pressor effect (Mitchell & Navar 1995), and it is very important in cell proliferation owing to its mitogenic actions (Gill et al 1977, Casellas et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Its regulatory actions are mediated by two pharmacologically distinguishable classes of G-protein-coupled cell-surface receptors (AT1 and AT2), of which the AT1 class has been now regarded as a mediator of the major pathophysiological actions of AngII (2). In the adrenals, locally formed AngII might play an important role as an autocrine or paracrine regulator of adrenal function, whereas an abnormal activity of the local renin-angiotensin system might be involved in the pathogenesis of abnormal adrenal growth, abnormal mineralocorticoid production, and hypertension (25). Therefore, similar to the constitutive activation of G-protein-coupled TSH and LH receptors by somatic mutations (7,8), a constitutive activation or a genetic variant of AT1 receptor could lead to increased AngII actions on target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley et al (1974) reported that T 4 -induced renal hypertrophy in vivo is associated with a rise in the mitotic index, and Stephan et al (1982) found an increase in DNA content. The mechanism is not fully understood, but participation of the RAS has been proposed, because AII is known to have potent cell proliferation effects in several tissues in vitro (Gill et al 1977) and in vivo (Casellas et al 1997). Kobori et al (1998) observed that T 4 produces renal hypertrophy in rats, with an increase in renal renin mRNA expression and in renal renin and AII levels.…”
Section: Renal Hypertrophymentioning
confidence: 99%